Late retinal redetachment due to proliferative vitreoretinopathy after more than one decade - Norlelawati Z,; Mae-Lynn Catherine Bastion, (Faculty of Medicine, Universiti Kebangsaan Malaysia Medical Centre, 2016)
A 44-year-old Malay lady presented with recent onset of inferior field defect for a week. Vision was 6/18, N18. She gave a history of myopia and two prior retinal detachment surgeries twelve years previously following which the retina was flat. Subsequently, the vision reduced to hand motions as the macula became involved. She then underwent successful re-attachment vitrectomy surgery for rhegmatogenous retinal detachment due to superior retinal breaks in association with proliferative vitreoretinopathy (PVR) Grade B. We share this interesting case of retinal redetachment in a previously vitrectomised eye that was stable during follow up for more than 10 years. This was associated with late onset PVR. Counselling of patients on the symptoms of redetachment due to late onset PVR is mandatory in patients after retinal detachment surgery.